Environmental protection - Mara, Wil. (New York : Scholastic, 2013)
The relationship between human progress and its effect on the natural environment has long been a contentious issue. This book details the history of the environmental movement in the United States, from its first stirrings in the writings of Henry David Thoreau and George Perkins Marsh to recent debates over climate change and energy sources.
Includes bibliographical references (p. 61) and index.
Keywords: Environmental protection -- United States -- Juvenile literature; United States -- Environmental conditions -- Juvenile literature